Serological and biochemical properties of the capsid and major noncapsid proteins of maize stripe, rice hoja blanca, and Echinochloa hoja blanca viruses - Falk, BW; Morales, Francisco José; Tsai, JH; Niessen, AI (Scientific Societies, 1987)
The two major virus-specific proteins found in plants infected by maize stripe virus (MStpV), rice hoja blanca virus (RHBV), and Echinochloa hoja blanca virus (EHBV) were compared by serological and one-dimensional peptide-mapping analysis. When total cellular proteins from healthy plants and plants singly infected with MStpV, RHBV, or EHBV were compared by SDS-PAGE, the samples from the virus-infected plants showed a prominent protein of about 32,000 Mr in the high-speed pellet fraction and a prominent protein of about 16,000 Mr in the high-speed supernatant fractions. These were identified as the virion capsid and virus-specific major noncapsid proteins, respectively. Antisera produced to these six proteins reacted specifically with virus-infected and not healthy plants by indirect ELISA. The two MStpV protein antisera reacted only with MStpV-infected plants, whereas the RHBV and EHBV protein antisera reacted with plants infected with either virus but not MStpV. Immunological analysis of Western blots showed that the antisera were specific in that none of the noncapsid protein antisera reacted with any of the capsid proteins and vice versa. One-dimensional peptide-mapping analysis of the individual proteins gave results that agreed with the serological data. The MStpV capsid and noncapsid proteins were distinct from the corresponding proteins of RHBV and EHBV, which were indistinguishable.